El asesor de ventas y el cliente céntrico como toma de decisiones en el Banco de Crédito del Perú, 2020 - Silva Estacio, Pedro Alexander (2021)
The document is structured in four chapters, the first one describes the institutional context of Banco de Crédito del Perú within the Peruvian financial system and then gives way to the commercial sector that is made up of personal banking, as well as the functions commissioned and carried out by according to the Organization and Functions Manual. The first chapter also identified the problems found in the workplace and the objectives of the report; both general and specific, using observation and documentary analysis as a study methodology. The second chapter presents the technical scientific foundation of job performance obtained at Banco de Crédito del Perú. In the theoretical framework, it was possible to collect information about similar problems, contributions and solutions. The third chapter describes the strategies for solving the problems identified, so that the fourth chapter details the critical appraisal based on the experience and training received in the professional school of Administration. Finally, based on the results obtained, the conclusions are detailed, one of the most important being the need to intensify soft skills development courses and advanced technical training in the Professional School of Administration. Faced with this situation, the contribution was to express a critical appreciation to the professional training of the Administration career based on my work experience, in order to be able to perform efficiently and competitively in any job related to Sales and Service Advisor.